Application of Data Matching Algorithm in Accounting Information System Assisting Enterprise Financial ERP System Stability Optimization - Xiong, Xiaoyan; Wei, Wenxiu (2022 International Conference on Edge Computing and Applications (ICECAA), 2022)
In this paper, study has been conducted on the application of the data matching algorithm in the accounting information system assisting enterprise financial ERP system stability optimization. Under the financial sharing model, enterprises should take "sharing to improve norms, and service to create value" as the strategic business goal, take "risk orientation, deepen application, process control, and accelerate results" as the main line, and fully integrate the concept of strengthening financial auditing into the financial system management and business activities. The main idea of the data set division method is to divide the unbalanced defect data set into multiple balanced defect data sets according to certain rules, and then train multiple classifiers on the balanced defect data sets and integrate them according to a certain learning method. Hence, with the integration of the mentioned models, the designed data matching algorithm is applied. Through the testing under different data sets, the optimization is conducted.